1988
DOI: 10.1096/fasebj.2.1.2891579
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐dependence to opioid and α 2 ‐adrenergic receptor agonists in NG108‐15 cells

Abstract: Clonidine, a partial alpha 2-agonist, has been used empirically to alleviate opiate withdrawal symptoms, but the mechanism of its effects is not completely understood. We studied the interactions of opioid and adrenergic receptor agonists in the NG108-15 cells, which are a model of opiate dependence. We determined that in these cells the adenylate cyclase (AC) [EC 4.6.1.1; ATP pyrophosphate-lyase (cyclizing) overshoot response to opioid or alpha 2-agonist withdrawal can be significantly attenuated or suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Moreover, abrupt withdrawal of opioids in dependent subjects causes the precipitation of abstinence syndrome which is a major problem in treating the condition of substance dependence (Williams et al 2001). Various pharmacological and non-pharmacological approaches are employed to control opioid withdrawal syndrome in man (Hardman et al 2001;Krantz and Mehler 2004;Lee et al 1987). However, none of the available options promises to conclusively treat the condition of opioid dependence and its related abstinence syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, abrupt withdrawal of opioids in dependent subjects causes the precipitation of abstinence syndrome which is a major problem in treating the condition of substance dependence (Williams et al 2001). Various pharmacological and non-pharmacological approaches are employed to control opioid withdrawal syndrome in man (Hardman et al 2001;Krantz and Mehler 2004;Lee et al 1987). However, none of the available options promises to conclusively treat the condition of opioid dependence and its related abstinence syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments in NG108-15 cells had shown prominent interactions between the opioid and the α 2 -adrenergic systems, including cross-dependence between morphine and clonidine (Lee et al, 1988) and yohimbine blockade of morphine-induced changes in the redox status of cells (Polanco et al, 2009). These interactions closely resemble in vivo conditions where qualitatively similar drug interactions have been observed regarding analgesia, toxicity, tolerance and dependence (reviewed in Alguacil and Morales, 2004), therefore suggesting that NG108-15 cells provide a useful model to investigate the molecular mechanisms involved.…”
Section: Discussionmentioning
confidence: 92%
“…The experiments performed so far on cAMP production strongly suggest that the interaction could happen at the level of adenylate cyclase regulation, since yohimbine effectively prevented the inhibitory effect of morphine on forskolininduced cAMP accumulation. Opioid receptors and α 2 -adrenoceptors are known to be negatively coupled to adenylate cyclase in NG108-15 cells (Sharma et al, 1975;Sabol and Nirenberg, 1979), and a significant interaction between ligands of both kind of receptors was observed by Lee et al (1988) when studying long-term regulation of adenylate cyclase activity. These authors reported that the cAMP overshoot induced by withdrawal from 48 h-incubation with morphine was attenuated by a short exposure to the α 2 -adrenoceptor agonist clonidine, whilst withdrawal from incubation with the α 2 -adrenoceptor agonist UK 14304 was similarly blocked by morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mathematical simulations have shown that, although several systems could share a common signalling pathway, they might have compartmentated intracellular access to second messengers, such as cyclase or GTPasas molecules 11 . 22,23,34,46 …”
Section: Interaction Between Opioid and Somatostatin Systemsmentioning
confidence: 99%